2015
DOI: 10.1142/s0218271815300074
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological evolution with interaction between dark energy and dark matter

Abstract: In this review we consider in detail different theoretical topics associated with interaction in the dark sector. We study linear and non-linear interactions which depend on the dark matter and dark energy densities. We consider a number of different models (including the holographic dark energy and dark energy in a fractal universe) with interacting dark energy (DE) and dark matter (DM), have done a thorough analysis of these models. The main task of this review was not only to give an idea about the modern s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
225
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(233 citation statements)
references
References 236 publications
(261 reference statements)
4
225
0
3
Order By: Relevance
“…(7)- (12). To prove this one can follow the calculations outlined in Appendix A assuming no interaction with the scalar field; see also [28].…”
Section: Lagrangian Formulation Of Relativistic Fluidsmentioning
confidence: 95%
See 2 more Smart Citations
“…(7)- (12). To prove this one can follow the calculations outlined in Appendix A assuming no interaction with the scalar field; see also [28].…”
Section: Lagrangian Formulation Of Relativistic Fluidsmentioning
confidence: 95%
“…Note however that if both dark matter and dark energy can be measured solely by their gravitational influence, then the physical consequences of their interaction might be observationally indistinguishable from similar effects arising in other cosmological models without interaction, as for example in modified gravity and warm dark matter models [9][10][11]. Nevertheless it is important to study different interacting dark energy models not only to search for new interesting phenomenological features, but also to support the observational efforts to focus on possible distinctive signatures of such models; a tentative review on these models has recently been proposed in [12] (see also [19]). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, discussed models of holographic dark energy models belongs to generalization considered in Reference [24] which allows us to unify symmetry in early universe and LSU in sense of accelerated expansion. In recent scientific literature there is an active interest towards in interacting DE models, which is a non-gravitational coupling between DE and DM revealing interesting symmetry [49] (and references therein). There are various forms of linear and non linear forms of interactions considered in modern cosmology.…”
Section: Eos Parameter Mattermentioning
confidence: 99%
“…[25] offers a recent review of this topic). Recently, the authors of [26] showed that this kind of interaction is favored by current cosmological observations in an extended ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%